Caution on the severe damage of Gelsemium elegans poisoning: a case report on family poisoning and systematic review - Zhao, Yawen; Shen, Bisheng; Xiao, Qimei; Wang, Yameng; Fu, Yi; Tang, Qi; Liang, Zhangrong (Frontiers in Public Health, 2025)
ObjectiveThis study reports a familial Gelsemium elegans poisoning case and systematically evaluates the efficacy of gastric lavage in G. elegans intoxication through a meta-analysis.MethodsWe systematically searched PubMed, Web of Science, CNKI, and Wanfang Data (2000–2024). Eligible randomized controlled trials and case reports comparing gastric lavage versus non-lavage approaches were included. Data were extracted from published studies, and pooled odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using Mantel–Haenszel random-effects models.ResultsThirteen studies involving 160 patients demonstrated an overall in-hospital mortality of 18.75%. Gastric lavage suggested potential survival benefit compared to controls (OR 0.39; 95% CI 0.15–0.99; p = 0.62).ConclusionG. elegans poisoning is life-threatening, with severe cases rapidly progressing to respiratory/circulatory failure requiring urgent support. Gastric lavage may offer survival advantage in hemodynamically stable patients when performed with airway protection. Prompt respiratory support should be prioritized in the therapeutic management.